THYROID DYSFUNCTION IN PATIENTS WITH TYPE 1 DIABETES AT A TERTIARY CARE HOSPITAL - KHAN, TZ; SHAH, SMU (Biological and Clinical Sciences Research Journal, 2024)
Individuals with diabetes mellitus (DM) are reporting thyroid dysfunction at an alarming rate, and there's evidence that thyroid dysfunction—whether overt or subclinical—affects overall glycaemic control. 12.3% of individuals with Type 1 DM have overt hypothyroidism, while around 24.8% of patients have abnormal thyroid autoantibody levels. Objective: This study aimed to determine Thyroid dysfunction in patients with type 1 diabetes at a tertiary care hospital. Methods: The present descriptive study was carried out at Hayatabad Medical Complex Peshawar from January 2024 to June 2024 after obtaining permission from the ethical committee of the institute. A total of 110 participants were enrolled in the study. We included all T1DM patients of both genders. All participants with T1DM visiting the OPD were screened. The primary test for assessing thyroid function was TSH, which has an acceptable range from 0.5 to 5 mIU/ml. Triiodothyronine (T3) and free thyroxin (FT4) levels were also measured. On a Cobos 6000 machine (Roche), thyroid function tests (TFTs) were performed. Data was analyzed through SPSS version 22.0. Results: A total of 110 participants of both genders of different age groups were enrolled in this study. 63.63% of them were females and 36.36% were males. 18 individuals (16.36%) had subclinical hypothyroidism, 14 individuals (12.7%) were hypothyroid, and 78 of them (70.90%) were euthyroid. We did not identify any occurrences of hyperthyroidism in current research. In comparison to the rest of the population, individuals with hypothyroidism had significantly different mean Thyroid stimulating hormone, FT4 and FT3 levels (p <0.0001). The mean differences for age, the period of diabetes, randomized blood sugar (RBS), and HbA1c were not statistically significant. When the data was examined for subclinical hypothyroidism, however, there was a substantial variance for mean Thyroid stimulating hormone (p <0.0001) but not for FT4 or FT3. Likewise, there was no difference seen in age (p= 0.35) or gender (p= 0.63). Conclusion: Type 1 diabetes individuals often suffer from thyroid dysfunctions particularly hypothyroidism (12.7%) and subclinical hypothyroidism (16.36%). The analysis of thyroid-stimulating hormone levels and other hormonal markers for thyroid function is the most crucial approach.